Struktur Anatomi Batang Empat Spesies Bambusa (B. maculata Widjaja, B. uetuldoide Widjaja, B. glaucophylla Widjaja dan B. multiplex Widjaja) di Kalimantan Barat - Riza Linda, Ica Adrianita Rahmi, Mukarlina (Jurnal Protobiont, 2015)
West Kalimantan is one of the Provinces with the spread of bamboo plants, one of which is a species of Bambusa. This research aims to know the stem anatomy structure of four species of Bambusa (B. maculata Widjaja, B. uetuldoide Widjaja , B. glaucophylla Widjaja and B. multiplex Widjaja). This researchwas carried out in June 2014 to October 2014. The study used two test samples i.e. bamboo shoots and bamboo culm. The bamboo culms used were the the node and the internode. The results showed that the four bamboo shoots and the stalks had a similar tissue structure that contains the epidermis, cortexand vascular bundle. Two types of bundles found were the vascular bundle type III and type IV. The vascular bundle type III is a type of vascular bundle that consists of two parts i.e. vascular bundle and one fiber bundle that can be found in B. maculata, B. uetoldoide and B. multiplex. The vascular bundle type IV is a type of vascular bundle that consists of a single vascular bundle and two fiber bundles that can be found in B. glaucophylla. The transverse incision of the bamboo culm on thepart of the internode showed that there is sclerenchymatic spathe and on the part of the node has no sclerenchymatic spathe and has two fiber that flanking the bundle.